Effect of Resveratrol on Hematological and Biochemical Alterations in Rats Exposed to Fluoride. (5th June 2014) - Atmaca, Nurgül; Yıldırım, Ebru; Güner, Bayram; Kabakçı, Ruhi; Bilmen, Fatih Sultan
Abstract : We investigated the protective effects of resveratrol on hematological and biochemical changes induced by fluoride in rats. A total of 28 rats were divided into 4 groups: control, resveratrol, fluoride, and fluoride/resveratrol ( n = 7 each), for a total of 21 days of treatment. Blood samples were taken and hematological and biochemical parameters were measured. Compared to the control group, the fluoride-treated group showed significant differences in several hematological parameters, including decreases in WBC, RBC, and PLT counts and neutrophil ratio. The group that received resveratrol alone showed a decrease in WBC count compared to the control group. Furthermore, in comparison to the control group, the fluoride group showed significantly increased ALT enzyme activity and decreased inorganic phosphorus level. The hematological and biochemical parameters in the fluoride + resveratrol treated group were similar to control group. In the fluoride + resveratrol group, resveratrol restored the changes observed following fluoride treatment, including decreased counts of WBC, RBC, and PLT, decreased neutrophil ratio and inorganic phosphorus levels, and elevated ALT enzyme activity. The present study showed that fluoride caused adverse effects in rats and that resveratrol reduced hematological and biochemical alterations produced by fluoride exposure.